Ultrastructural changes in the kidney of rats with acute exposure to cadmium and effects of exogenous metallothionein - Kukner, Aysel; Colakoglu, Neriman; Kara, Haki; Oner, Hakan; Ozogul, Candan; Ozan, Enver (Springernature, 2007)
Ultrastructural changes in the kidneys of rats after acute cadmium exposure and the effects of exogenous metallothionein (MT) were studied by transmission electron microscopy. Thirty-six adult Wistar rats were divided into three groups. Cadmium chloride (CdCl2) (3.5 mg/kg/day) was injected subcutaneously in the first group. In the second group, 30 mu mol/kg MT was administered in addition to CdCl2. Control rats received 0.5 ml subcutaneous saline solution. Four rats from each group were killed on days 1, 3, 5, and 7 after administration of the compounds. Kidney tissues were taken and fixed in 2.5% glutaraldehyde solution for electron microscopic observations. Tissue damage in kidney increased as time passed since the administration of CdCl2 in the first group. Degeneration in the proximal and distal tubules was observed. Increased apoptosis was seen in the proximal tubules epithelium, especially on day 7. Peritubular capillaries became dilated, there was degeneration of the endothelial cells, and the amount of intertubular collagen fibers was increased. On day 1, irregular microvilli in the proximal tubules, deepening of the basal striations, and myelin figures; on day 3, multiple vesicular mitochondria and regions of edema around tubules; on days 5 and 7, increased apoptotic cell in the proximal tubules and widened rough endoplasmic reticulum of the endothelial cells of glomerular capillaries were observed. We observed that the structural alterations that increased depending on the day of Cd administration decreased after exogenous MT administration, the dilation of the peritubular capillaries persisted, and there were degenerated proximal tubules. It was established that cadmium chloride was toxic for kidney cortex and caused structural damage. Exogenous MT partly prevents CdCl2-induced damage.
Keywords: cadmium chloride; metallothionein; kidney